2014
DOI: 10.1111/jora.12074
|View full text |Cite
|
Sign up to set email alerts
|

Disengagement From Gangs as Role Transitions

Abstract: Most research has focused on the onset and consequences of gang membership, neglecting the importance of leaving the gang. Disengagement from gangs often occurs during the transition to adulthood, a critical period of the life course. While leaving gangs has received growing attention over the past decade, absent from this research has been a suitable theoretical perspective with which to frame disengagement. This study drew on Ebaugh's theory of role exit to examine disengagement among 260 former gang members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
131
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 60 publications
4
131
1
Order By: Relevance
“…Criminology has developed a rich body of research related to desistance, built on life-course theory, which may have direct relevance for counter-radicalisation (Bottoms et al, 2004;Decker et al, 2014;LaFree and Miller, 2008;McNeill, 2012;Shapland and Bottoms, 2011).…”
Section: Many Of the Factors And Processes Involved In Leaving Terrormentioning
confidence: 99%
“…Criminology has developed a rich body of research related to desistance, built on life-course theory, which may have direct relevance for counter-radicalisation (Bottoms et al, 2004;Decker et al, 2014;LaFree and Miller, 2008;McNeill, 2012;Shapland and Bottoms, 2011).…”
Section: Many Of the Factors And Processes Involved In Leaving Terrormentioning
confidence: 99%
“…Individuals fluctuated between the stages of being "completely in" the gang, "first doubts", "anticipatory socialisation", "turning points" and being "completely out" of the gang 18:273 . First doubts start in the back of the individual's mind and gradually become more prominent, for example, having doubts about the gang lifestyle 18 . Anticipatory socialisation entails a process of role experimentation such as joining a gang outreach programme or trying to become a better parent by severing ties with the gang.…”
Section: Disengaging From Gangsmentioning
confidence: 99%
“…Much of the previous research with gang-involved youth was conducted in the United States of America (USA), and has shown that leaving a gang, also known as gang disengagement or desistance, may be a long and challenging process with many failures and obstacles 17,18 . Pyrooz and Decker examined the motives for leaving a gang which they termed "push and pull factors" 17:420 .…”
Section: Disengaging From Gangsmentioning
confidence: 99%
See 2 more Smart Citations